Considering selection pressures for identity fusion and self-sacrifice in small-scale societies. (27th December 2018) - Wiessner, Polly
Abstract: Whitehouse's view that our ultrasocial species evolved in small, warring bands is questioned, and alternative social selection pressures for the evolution of identity fusion and self-sacrifice in small-scale societies are proposed. Short durations of states of fusion allow for re-evaluation of risks; the consolidation of episodic memories into collective oral traditions elicits cooperation. Dysmorphic memories may be more powerful in generating identity fusion when followed by euphoric ones, as in "rites of torture" in male initiations.